A population history of the United States - Klein, Herbert S. (Cambridge University Press, 2004)
This is the first full-scale one-volume survey of the demographic history of the United States. From the arrival of humans in the Western Hemisphere to the current century, Klein analyzes the basic demographic trends in the growth of the pre-conquest, colonial and national populations. He surveys the origin and distribution of the Native Americans, the post-conquest free and servile European and African colonial populations and the variation in regional patterns of fertility and mortality to 1800. He then explores trends in births, deaths, international and internal migrations in the nineteenth century and compares them with contemporary European developments. The profound impact of historic declines in disease and mortality on the structure of the late twentieth century population is explained. Finally the late twentieth century changes in family structure, fertility and mortality are evaluated for their influence on the evolution of the national population for the 21st century.